2015
DOI: 10.1007/s13139-015-0356-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Sensitivity and Quantitative Indices Between 68Ga-DOTATOC PET/CT and 111In-Pentetreotide SPECT/CT in Neuroendocrine Tumors: a Preliminary Report

Abstract: Ga-DOTATOC PET/CT has a higher diagnostic sensitivity than (111)In-pentetreotide scans with SPECT/CT. The TNR on PET/CT is higher than that of SPECT/CT, which also suggests the higher sensitivity of PET/CT. (111)In-pentetreotide SPECT/CT should be used carefully if it is used instead of (68)Ga-DOTATOC PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…Therefore, the affinity of these tracers for DAT is identical (Seo et al, ). When compared with SPECT, PET has higher spatial resolution and higher sensitivity to signal, which produces better image quality for analysis (Lee et al, ). The SBR on SPECT may be underestimated because of the method of attenuation correction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the affinity of these tracers for DAT is identical (Seo et al, ). When compared with SPECT, PET has higher spatial resolution and higher sensitivity to signal, which produces better image quality for analysis (Lee et al, ). The SBR on SPECT may be underestimated because of the method of attenuation correction.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, 111 In-labelled somatostatin analogues are no longer used in the diagnostics of NENs. In clinical practice, commonly used are 99m Tc-labelled agonists of somatostatin receptors: 99mTc-HYNIC-TATE and 99m Tc-EDDA/HYNIC-TOC, both characterised by a similar sensitivity in the imaging of NENs [51].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…The sensitivity of SRI depends on the method (it is the highest in PET/CT examination). For most types of GEP NET and locations the SRI sensitivity images between 54 and 100% [107][108][109][110][111][112][113][114][115]. Insulinoma is an exception, as somatostatin receptor overexpression is found in 50-60% of cases [116].…”
Section: Radioisotope-labelled Somatostatin Analogues Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine tumor scan was performed in a small number of cases of neuroendocrine tumors in 2013 in Korea: 314 MIBG SPECT cases (154 cases in combination with SPECT/CT) and 33 octreotide SPECT cases (13 cases in combination with SPECT/CT) [2]. Recent studies reported that PET/CT using Ga-DOTA peptide has better diagnostic accuracy than octreotide scintigraphy in patients with neuroendocrine tumors [27,28]. However, since Ga-DOTA peptide is not extensively used in Korea, SPECT and SPECT/CT using somatostatin receptors are still valuable imaging methods for the diagnosis and treatment of neuroendocrine tumors.…”
Section: Neuroendocrine Tumormentioning
confidence: 99%